The Creativity out of Insecurity and Uncertainty through the Perspective of Realism in Crane’s The Red Badge of Courage - Hasobi, Wael Fadhil (South Asian Journal of Social Sciences and Humanities, 2024)
In this paper I intend to discuss realism in Stephen Crane’s The Red Badge of Courage .Although it is purely a work of Crane’s imagination, it is universally recognized as a greater work of art. The novel revolves mainly round the fear-inspired actions and deeply agitated mind of Henry Fleming, the protagonist of the novel. The novel deals with the theme of war and violence that leads to recognize the naturalistic view of the impact of the external forces on human destiny in which it leads to the concept of realism in life through war as a metaphor of life with its ambivalences, morality and alienation.